(untitled) (Jurnal Inovasi Sekolah Dasar, 2026)
This research aims to determine parents’ attention to students’ mathematics learning outcomes based on Piaget’s theory of cognitive development and the involvement of students’ parents to analyze how parents pay attention to students’ mathematics learning outcomes. This type of research is qualitative with a case study approach. The subjects of this research were 14 parents representing 25 students in class V-A UPTD SD Negeri 08 Sisumut T.A 2024/2025. The data collection technique is a multiple choice test with 18 questions as well as student report cards and interviews with parents of class V students. The results of the research show that parents who have high attention do not guarantee that children will have high learning outcomes, in fact some their children have low learning outcomes. However, it can also be seen that parents who provide good attention also have a good impact on children, which shows that children’s math scores are high. And conversely, parents who give poor attention to their children show that their children’s math scores are relatively low.